2017
DOI: 10.1080/10937404.2017.1305924
|View full text |Cite
|
Sign up to set email alerts
|

Engineered nanomaterial-induced lysosomal membrane permeabilization and anti-cathepsin agents

Abstract: Engineered nanomaterials (ENMs), or small anthropogenic particles approximately < 100 nm in size and of various shapes and compositions, are increasingly incorporated into commercial products and used for industrial and medical purposes. There is an exposure risk to both the population at large and individuals in the workplace with inhalation exposures to ENMs being a primary concern. Further, there is increasing evidence to suggest that certain ENMs may represent a significant health risk, and many of these E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 167 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…All of these parameters including residual metal catalysts, surface functionalization, dispersal, and surface reactivity have been shown to impact their bioactivity as assessed using in vitro screening assays and following short-term in vivo exposures in mice [51, 52, 56, 85, 86]. Physicochemical properties of carbon nanotubes, especially length, diameter, and flexibility have been shown to be critical for uptake by target cells, lysosomal membrane permeabilization, inflammasome activation, and release of mature IL-1β that triggers recruitment of additional inflammatory cells into the lungs [50, 52, 87]. Theoretical modeling studies have been developed to predict potential lung toxicity of high aspect ratio nanomaterials based on their nanomechanical properties [88, 89].…”
Section: Discussionmentioning
confidence: 99%
“…All of these parameters including residual metal catalysts, surface functionalization, dispersal, and surface reactivity have been shown to impact their bioactivity as assessed using in vitro screening assays and following short-term in vivo exposures in mice [51, 52, 56, 85, 86]. Physicochemical properties of carbon nanotubes, especially length, diameter, and flexibility have been shown to be critical for uptake by target cells, lysosomal membrane permeabilization, inflammasome activation, and release of mature IL-1β that triggers recruitment of additional inflammatory cells into the lungs [50, 52, 87]. Theoretical modeling studies have been developed to predict potential lung toxicity of high aspect ratio nanomaterials based on their nanomechanical properties [88, 89].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc oxide (ZnO), titanium dioxide (TiO 2 ), and cerium oxide (CeO 2 ) nanoparticles have been frequently used in consumer products [ 3 ], consequently, their widespread use increases the likelihood that these materials will result in human exposures [ 4 ]. Many studies have reported that some NP have the potential to cause toxicity and inflammation [ 5 , 6 , 7 , 8 , 9 ] following NRLP3 inflammasome activation [ 10 , 11 , 12 ]. Alveolar macrophages (AM) are the key innate immune cells in lungs responsible for the recognition and removal of inhaled particles that can lead to NLRP3 inflammasome activtion [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that some NP have the potential to cause toxicity and inflammation [ 5 , 6 , 7 , 8 , 9 ] following NRLP3 inflammasome activation [ 10 , 11 , 12 ]. Alveolar macrophages (AM) are the key innate immune cells in lungs responsible for the recognition and removal of inhaled particles that can lead to NLRP3 inflammasome activtion [ 5 , 11 ]. However, the mechanisms accounting for how NP or common micron-sized particles such as respirable crystalline silica (SiO 2 , which is known to cause silicosis) activate the NLRP3 inflammasome remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although precipitation as a sulfide strongly reduces the activity of ionic silver (15), sulfidation is a complex redox reaction that can generate radicals (29) and deplete H 2 S, a signaling molecule with antioxidant properties (30). Second, membrane puncturing could release lysosomal contents including acids and proteases that can initiate stress responses (31). Indeed, AgNWs are more effective than Ag nanoparticles at the induction of NLRP3 inflammasome activation and IL-1β production in phagocytes but until now a mechanism for membrane damage has not been clearly revealed (32, 33).…”
mentioning
confidence: 99%